PENGARUH INTENSITAS PENGGUNAAN ARTIFICIAL INTELLIGENCE (AI) TERHADAP KEMAMPUAN BERPIKIR KOMPUTASIONAL DAN LITERASI DIGITAL MAHASISWA PENDIDIKAN GURU MADRASAH IBTIDAIYAH (PGMI) - Inayati, Ummi; Agustina, Lina; Husna Zahrotus Septiana, Amalia; Rhohmah, Isnatur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of technology in the Society 5.0 era has increased the use of Artificial Intelligence (AI) in higher education, raising concerns about its impact on students’ computational thinking skills and digital literacy. This study aims to examine the influence and relationship between the intensity of AI usage and computational thinking as well as digital literacy among students of Islamic Elementary Teacher Education (PGMI) at Institut Attanwir Bojonegoro. A quantitative correlational design was employed involving 114 undergraduate PGMI students from various semesters. Data were collected through validated and reliable questionnaires measuring AI usage intensity, computational thinking skills, and digital literacy. Data analysis was conducted using Spearman’s rank correlation and simple linear regression. The results indicate that AI usage intensity has a positive and significant relationship with computational thinking skills, although the correlation is weak (r = 0.220) with a contribution of 3.6%. Conversely, AI usage intensity does not show a significant relationship or effect on students’ digital literacy. These findings suggest that while AI can support the development of computational thinking when used appropriately, it does not automatically enhance digital literacy. Therefore, pedagogical integration, critical engagement, and ethical guidance are essential to optimize the role of AI in developing students’ 21st-century competencies.